Beyond compliance: Participation, co-production and change in justice sanctions1. (April 2015) - McCulloch, Trish
This article explores the place and potential of a more participatory and co-productive justice practice, using the particular lens of compliance. In recent years, compliance has come to be associated with new managerial and correctional forms of justice. Yet, emerging theoretical and empirical analyses attest that individual compliance is a complex and multi-dimensional dynamic. It is not particularly responsive to mechanisms of enforcement and control, and where enforced compliance is achieved it does not emerge as a particularly valuable justice outcome. These findings, and others, suggest the relevance of a more co-productive justice pursuit – one that recognises and supports the participation, potential and progression of those required to comply.